Pengaruh Word Of Mouth, Pengetahuan Produk Dan Citra Merek Terhadap Minat Pembelian Ipad Di Kota Surabaya - Vierri Lipsendy Lo; Iswati Iswati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Nowadays technological developments, there are various kinds of technology circulating in society. Various examples of technology that have been circulating include computers, mobile phones, smart watch and tablets. Various examples of technology that have been circulating include computers, mobile phones, smart watch and tablets. There is one tablet brand that has been circulating among the public. One of them is the Apple company with their tablet product iPad. This study aims to determine and analyze the influence of word of mouth, product knowledge and brand image on iPad purchase interest in the city of Surabaya. This research is based on iPad purchase interest that is increasing from year to year and is based on purchase interest that occurs before the purchase of the product. This study used non-probability sampling and had a response of 150. The sample is taken through the number of indicators times the parameter 10. The analysis method used in this study is PLS-SEM (Structural Equation Model based on Partial Least Square). The results of this study show a significant influence of word of mouth on purchase interest, a significant influence of product knowledge on purchase interest and a significant influence of brand image on purchase interest.